Supply Chain Resilience: The Role of Total Quality Management on the Performance of Kenya Medical Supplies Authority - Ndungu, Wahome John; Muathe, Stephen Makau (European Scientific Journal, ESJ, 2025)
Managers are empowered to improve the quality of services and products by incorporating key total quality management principles. However, the Kenya Medical Supplies Authority (KEMSA) has faced scrutiny due to inefficiencies, which are hindering access to essential healthcare services. This aims to assess the Kenya Medical Supplies Authority’s performance in the application of the four Total Quality Management principles. These are fact-based decisions, process-centric approaches, relationship management, and employee engagement. The study is grounded in four theoretical foundations: resource-based view, dynamic capabilities, stakeholder theories, and Deming’s theory of quality management. A descriptive research design was used. The target population was 330 employees; however, a sample of 181 respondents was selected using proportionate stratified and simple random sampling techniques. Structured questionnaires were used to collect data, which was analyzed quantitatively using both descriptive and regression analysis, and SPSS version 25 was used to aid the data analysis. The findings indicate that the independent variables explain 58.5% of variables in the dependent variable, that is, the performance of KEMSA. Fact-based decisions had the highest impact and positive correlation with performance (B = 0.372, t = 5.239), followed by employee engagement (B = 0.348, t = 4.640), process-centric approach (B = 0.319, t = 4.691), and relationship management (B = 0.257, t = 3.134 all at p<0.01. The findings point to the importance of continuous staff training, participatory leadership, and integrated data systems to enhance performance. Additionally, the study recommends mentorship for junior staff, regular assessment of all resources, and a supportive organizational culture that sustains quality improvements.